PENGARUH CAPITAL INTENSITY, UKURAN PERUSAHAAN, DAN LEVERAGE TERHADAP TAX AVOIDANCE PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX - Nawang Kalbuana; Rinosa Ari Widagdo; Devia Rahma Yanti (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2020)
The purpose of this study was to find out the effect of tax avoidance on capital intensity variables, company size, and leverage. Samples from this study are companies registered in Jakarta Islamic Index from 2015 to 2019. This research uses a purposive sampling technique in determining the sample while performing analysis used multiple linear analyses. The results of this study revealed that in companies registered in Jakarta Islamic Index on capital intensity variables have a positive influence on tax avoidance while leverage has a negative influence on tax avoidance. Another thing that is quite surprising in this research is the variable size of the company, especially in companies listed in Jakarta Islamic Index does not affect tax avoidance.